Algal Growth Enhances Light-Mediated Limitation of Bacterial Nitrification in an Aquaculture System - Wu, Dingxin; Cheng, Minling; Zhao, Shumiao; Peng, Nan; Hu, Ronggui; Hu, Jinlong; Liang, Yunxiang (Water, air, and soil pollution, 2020)
The accumulation of ammonia and nitrite in natural water and aquaculture systems would suppresses the immune system of aquatic animal and reduces the fish growth. Nitrifying bacteria have been widely used to reduce the accumulation of ammonia and nitrite in aquaculture systems, but are still ineffective in many cases. An aquaculture model system consisting of red crucian carp, algae, nitrifying bacteria, and pond water from a natural fish culture was established to explore the limitation of algae and light to nitrifying bacteria content and bacterial nitrification in the presence of a predator. The concentrations of nitrifying bacteria and bacterial nitrification in the group containing algae and light were significantly limited, and addition of nitrifying bacteria in algae groups had little effect. In algae-free groups, the concentrations of ammonia and nitrite were decreased by nitrifying bacteria, and the potential ammonia oxidization rate was also increased. Our findings reveal that the combined effects of algae growth and light exposure are responsible for the observed ineffectiveness of nitrifying bacteria in natural aquaculture environments.